Social-cultural aspects of the functioning of an institutional network, which is the base for the regional pro-innovating strategy implementation - Jan Stachowicz; Joanna Machnik-Slomka; Marek Kazmierczak (European Regional Science Association (ERSA), 2002)
A technology transfer is a key to an efficient innovating strategy implementation process. The institutional network should support this process. The aim of the paper is to point out the 'soft' circumstances which appear when institutions start to co-operate in such network. Furthermore some directions will be given how to face with negative circumstances. In the first part of the paper the social cultural aspects of cooperation between institutions within the network will be presented. The analyse will be mainly focused on processes of autonomisation and enclosing on an external cooperation in these institutions. The second part of the paper is a case study. A creation process of technological parks at the Silesian region will be analysed. Using this example the methods of dealing with difficulties which are discussed will be demonstrated.
Keywords: 330